How the Military Conflict in Eastern Europe Affected the Automotive Sector - Case Study Poland - Jaromir MYSŁOWSKI; Wojciech LEWICKI (Communications of International Proceedings, 2022)
The available literature on the subject emphasizes that contemporary armed conflicts are related to economic and business aspects as never before. The aim of the research is to present the current challenges to counter the crisis in this difficult economic and social period on the example of a selected market sector. Therefore, the article presents the results of research on the impact of armed conflict on the automotive sector in the case study - Poland. In particular, an attempt was made to identify the changes taking place in the sales and distribution systems of new and used passenger cars and spare parts, as well as the offered maintenance and repair services. This research may contribute to faster development of universal solutions in the field of counteracting the progressing crisis by identifying areas requiring adaptation to new market rules. In addition, the presented and interpreted results may constitute the basis and incentive for further research on the topic related to the impact of armed conflict on this industry in terms of identifying further socio-economic consequences for all stakeholders of this market.
Keywords: automotive sector; market research; crisis; technological changes.